Eco-friendly bio-dyeing of bio-treated nylon fabric using Esfand (P. harmala) based yellow natural colorant. (April 2022) - Adeel, Shahid; Hasan, Mahmood ul; Batool, Fatima; Ozomay, Meral; Hosseinnezhad, Mozhgan; Amin, Nimra; Hussaan, Muhammad
The ongoing age is the time of sustainability, where in the current pandemic scenario, which is getting worse, needs treatment with nature rather than chemical-based products. In this study, microwaves (M.W. rays) treatments as extraction mode for Esfand ( P. harmala ) have been revived for polyamide (nylon) dyeing. The water solubilized and acid solubilized filtrates and polyamide (nylon fabrics) were treated M.W. rays up to 10 min with an interval of 2 min. Mordanting with chemicals and plant extracts before and after dyeing was done at 60°C–80°C. It has been found the application of M.W. ray treatment for 4 min., to 30 mL of extract of 8 p H containing 4 g/100 mL of Table salt as leveling agent has given desired results when employed at 55°C for 55 min. Statistical analysis of dyeing variables through R.S.M., and two way-Anova shows that the effect of these variables has been observed highly significant. Experimentally it has been observed that the application of extract for dyeing of polyamide (nylon fabric) has given good results when chemical or bio-mordanted at selected conditions. Practically, Esfand seeds has ability for bio- coloration of surface modified polyamide fabric (nylon fabric), and utilization of pomegranate extract as bio-mordant and tannic acid as sustainable chemical mordant has furnished colorfast shades.